2016
DOI: 10.1111/ctr.12683
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐transplant wasting (as measured by muscle index) is a novel prognostic indicator in lung transplantation

Abstract: Low muscle index at lung transplantation is associated with worse survival and increased hospital LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 52 publications
2
61
3
Order By: Relevance
“…These findings are consistent with previous reports in patient populations undergoing major surgical procedures such as general surgery, liver and renal transplantation where core muscle size from abdominal CT was associated with longer hospital stay, higher rates of infection, and increased rates of post‐transplant mortality . In lung transplantation, pre‐transplant abdominal muscle CSA has been shown to be associated with ICU and hospital length of stay . Kelm et al .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with previous reports in patient populations undergoing major surgical procedures such as general surgery, liver and renal transplantation where core muscle size from abdominal CT was associated with longer hospital stay, higher rates of infection, and increased rates of post‐transplant mortality . In lung transplantation, pre‐transplant abdominal muscle CSA has been shown to be associated with ICU and hospital length of stay . Kelm et al .…”
Section: Discussionsupporting
confidence: 91%
“…Kelm et al . observed that muscle CSA was associated with three‐year survival in a selected sample of 36 lung transplant recipients with available abdominal CT scans. This is in contrast to the present study and that of Weig et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The inter‐rater agreement has previously been demonstrated to be excellent. Kelm et al reported the inter‐rater Pearson correlation coefficient ( r ) for muscle index measurements to be 0.998 (95% CI, 0.997‐ 0.999) . We calculated body surface area with the Mosteller formula: body surface area in m 2 = (height in cm × weight in kg/3600) 1/2 .…”
Section: Methodsmentioning
confidence: 99%
“…2 Biomarkers for frailty have been suggested, based on the concept that aging represents a low-grade chronic inflammatory process, sometimes termed "inflammaging." 13 Sarcopenia, like frailty, may be a risk factor for worse outcomes in lung transplant candidates; however, data are conflicting, with some studies showing lower pretransplant skeletal muscle mass measured radiographically being a risk factor for worse outcomes, 9,14 and others showing risk for longer hospital stays but not mortality. [3][4][5] Sarcopenia (loss of skeletal muscle mass) may be a precursor to the development of frailty and its adverse health outcomes.…”
Section: Pathophys Iology Of Fr Ailt Ymentioning
confidence: 99%